Developing and characterizing antioxidants and proteins from corn and its co-coproducts - Hu, Ruijia (Kansas State University, 2023)
Corn is one of the most cultivated crops worldwide and is an important source of food, feed, and biofuel in the U.S. It is considered an important source of protein and calories for millions of people in the world, especially people in Latin America, Africa, and Asia. Protein content in corn kernels varies among varieties and can be around 8-15%. Among the major cereals, corn is plentiful, cheap, and easily available, and has high phenolic content. It contains up to three times more phenolics compared to wheat, rice, and oats, and exerts the highest antioxidant activity. With the increase in ethanol production in the United States, more corn products are generated each year. Corn dried distillers’ grains (e.g., DDGS) are one of the major protein-rich co-products from corn dry milling processing, which are potential sources to produce high-value phenolic compounds and bioactive protein hydrolysates. However, limited information is available on the production and antioxidant performance of corn and corn DDGS antioxidants. The objectives of this dissertation were to produce both phenolic and protein hydrolysates from different varieties of corn and corn DDGS via different treatments and characterize their antioxidant performances with chemical assays and in different model systems. In the first study, seventeen different varieties of corn were screened and evaluated for their antioxidant compositions and properties. Those corn kernels had different colors and belonged to three different types including field corn (also called dent corn), popcorn, and sweetcorn. Both free and bound phenolics were extracted. Various assays were used to assess their antioxidant potentials. UPLC-DAD-ESI-Q-TOF-MS/MS was used for the characterization and quantification of the phenolic compounds. This section provides detailed understanding on the phenolic content and composition of different varieties of corn, as well as antioxidant activity using advanced instruments and comprehensive analysis. Based on the first study, four varieties of corn (Hickory king white, Reids yellow dent, Jimmy red, and Ohio blue) were further selected for distilled spirit production with four yeast strains from the species of Saccharomyces cerevisiae, including Safspirit GR-2 (GR-2), Red Star Distillers’ active dry yeast (DADY), SafSpirit HG-1 (HG-1), and SafSpirit USW-6 (USW-6). Phenolic compounds were extracted from both the original corn kernels and DDGS and thoroughly characterized. Results showed that both corn variety and yeast strains significantly (p < 0.05) influenced the total phenolic content (TPC), and DDGS possessed three to four times higher TPC than the unfermented corn. The GR-2 and HG-1 showed better improvement on TPC than other yeasts, and DDGS from blue corn indicated the highest free phenolic content up to 2078.82 mg/g GAE. Moreover, the phenolic profile was changed after fermentation. The DPPH+ and ABTS•+ scavenging activities of phenolic compounds were also improved after fermentation. In the third study, a sequential preparation procedure of phenolic antioxidants and protein hydrolysate antioxidants was developed. The antioxidant potential of the antioxidants was determined using different chemical assays, and the antioxidant performance of selected antioxidants in o/w emulsions was also evaluated. First, five GRAS organic solvents at 50% (v/v) were used to extract phenolic compounds from DDGS including acetone, ethanol, methanol, 1-proponal, and 2-propnal. The extracted phenolics were named Phenolic-A, Phenolic-E, Phenolic-M, Phenolic-1P, and Phenolic-2P, respectively. The residues were then hydrolyzed using 0.1 AU/g of Alcalase, and the prepared protein hydrolysates were named Hydrolysate-A, Hydrolysate-E, Hydrolysate-M, Hydrolysate-1P, and Hydrolysate-2P, respectively. The phenolic antioxidants showed significantly higher TPC than hydrolysate antioxidants, and the highest was observed on Phenolic-A (67.54 mg GAE/g). According to the results of composition and phenolic profile determined using the UPLC-DAD-ESI-Q-TOF-MS/MS, extraction solvent was critical to the phenolic acid yield and composition. The hydrolysate antioxidants showed a degree of hydrolysis in the range of 6.39-7.60%, and no significant difference was observed in the peptide content (501.58 -532.69 mg/g) as well as molecular weight distribution. Both phenolic and hydrolysate antioxidants had high antioxidant capacity against DPPH free radical scavenging and ferrous ion chelating. Considering the yield and antioxidant activities, 50% (v/v) of acetone and 50% (v/v) ethanol were the most efficient in producing antioxidants with promising antioxidant capacity. Phenolic-A, Phenolic-E, Hydrolysate-A, and Hydrolysate-E were added into oil in water (o/w) emulsions at both 1.0 and 2.5 mg/mL to evaluate their antioxidant performance. The selected phenolic and hydrolysate showed high efficiency in the prevention of lipid oxidation, and higher dosage showed relatively better prevention which was even better than 1 mg/mL rosemary extract. The results provide evidence that corn DDGS is a potential source of natural antioxidants, and sequential extraction would be a potential way to produce both corn phenolic and peptide antioxidants. The last study was focused on the preparation and characterization of corn protein concentrate from corn flour and DDGS. This study was conducted with a sequential extraction procedure combined with wet milling followed by physical treatments (sonication and homogenization), and then enzyme hydrolysis ([alpha]-amylase and cellulase) to produce concentrated proteins from corn flour and corn DDGS. The extracted proteins possessed a much higher protein content compared to the starting material with high protein recovery. Due to higher protein content in proteins produced from wet-milled corn flour with centrifuge or starch tabling and then followed by other treatments (protein-MC and protein-MT), more rupture of proteins was caused during future extractions inducing unfolding of protein structures and the consequent exposure of hydrophobic groups and regions buried inside. Therefore, protein-MC and protein-MT showed a relatively higher content of random coil (40.84% and 37.53%, respectively), higher SDS binding capacity (41.45 and 39.58 [mu]g/mg, respectively), and higher free SH groups (3.04 and 3.14 [mu]mol/g, respectively) and bond SS (14.71 and 15.41 [mu]mol/g, respectively) among all prepared proetins. Protein extracted from corn flour (Protein-flour) showed the highest water holding capacity (WHC) with a value of 4.70 g/g, Protein-MC had the second lowest WHC which was 3.17 g/g, and protein-MT had the lowest WHC of 2.91 g/g. The highest oil holding capacity (OHC) was observed on protein-MC, protein-MT, and protein-CD which were 3.52, 3.36, and 3.55 g/g, respectively. However, no significant difference was observed in the in vitro protein digestibility (83.13-85.03%). Overall, this study generates useful knowledge for producing antioxidative phenolics and protein hydrolysate/protein concentrate from corn and corn DDGS. It revealed that phenolic compounds and bioactive hydrolysates from corn could inhibit lipid oxidation through scavenging free radicals as well as chelating metal ions. Those novel applications could add value to the co-products from corn processing industries and provide alternative naturally derived antioxidant options for food, pet food, and animal feed uses.
Keywords: Corn-coproducts; Antioxidants; Phenolics; ProteinsCorn